Laporan survey biaja produksi industri tekstil di Sulawesi Selatan, Pebruari 1972 (Departemen Perindustrian, Direktorat Djenderal Perindustrian Tekstil, 1972)
Survey report on production costs of the textile industries in South Sulawesi.